Social And Spirit Goals: The Communication Strategy of Da’wah Activities One Day One Juz (ODOJ) Program in Palembang - Ramadoni, Muhamad Afdoli; Syarifudin, Achmad; Nuraida, Nuraida; Hamandia, Muhammad Randicha; Yulianti, Riza Randicha (Ath Thariq Jurnal Dakwah dan Komunikasi, 2024)
This research seeks to reveal the Da'wah Communication Strategy in the One Day One Juz (ODOJ) Program in Palembang. So, the question arises in this article by trying to answer what is the One Day One Juz Community (ODOJ) communication strategy for da'wah in Palembang? This type of research is field research with a qualitative approach and analyzed using descriptive qualitative. The author uses observation, interview and documentation techniques for data collection. Honed in writing through the Drive Theory by Morgan et al, this theory is described as the drive theory of motivation. According to Morgan, behavior is driven towards a goal by a drive condition within humans. The One Day One Juz program motivates members to get closer to the Al-Qur'an and be able to istiqomah read the Al-Qur'an every day. The results of this research show that the One Day One Juz program is a recitation program with a target of reading one Juz of the Al-Qur'an one day. The da'wah communication strategy carried out by the ODOJ Palembang community always invites its members to actively participate in activities, creating special groups for brothers and sisters to communicate information, advice and motivation. The ODOJ community has inhibiting factors, namely human resource factors from administrators and members and the community, factors where activities take place.